Orexin System: The Key for a Healthy Life - Chieffi, Sergio; Carotenuto, Marco; Monda, Vincenzo; Valenzano, Anna; Villano, Ines; Precenzano, Francesco; Tafuri, Domenico; Salerno, Monica; Filippi, Nicola; Nuccio, Francesco; Ruberto, Maria; De Luca, Vincenzo; et al. (Frontiers in Physiology, 2017)
The orexin-A/hypocretin-1 and orexin-B/hypocretin-2 are neuropeptides synthesized by a cluster of neurons in the lateral hypothalamus and perifornical area. Orexin neurons receive a variety of signals related to environmental, physiological and emotional stimuli, and project broadly to the entire CNS. Orexin neurons are “multi-tasking” neurons regulating a set of vital body functions, including sleep/wake states, feeding behaviour, energy homeostasis, reward systems, cognition and mood. Furthermore, a dysfunction of orexinergic system may underlie different pathological conditions. The selective loss orexin neurons was found in narcolepsia, supporting the crucial role of orexins in maintaining wakefulness. In animal models, orexin deficiency lead to obesity even if the consume of calories is lower than wildtype counterpart. Reduced physical activity appears the main cause of weight gain in these models resulting in energy imbalance. Interestingly, orexinergic neurons show connections to regions involved in cognition and mood regulation, including hippocampus. Orexins enhance hippocampal neurogenesis and improve spatial learning and memory abilities, and mood. Conversely, orexin deficiency results in learning and memory deficits, and depression.